Penggunaan metode structural equation modelling untuk menganalisis pengaruh dukungan teman sebaya dan self-efficacy terhadap motivasi berprestasi siswa - Naufal Rizqullah; Arif Hidayatullah; Heri Bastian; Yayat Maskopo (Universitas Sultan Ageng Tirtayasa, 2023)
the purpose of this study was to determine whether there is a significant influence on peer support and self-efficacy on student achievement motivation. the number of samples in this study were 206 students in several SMA and SMK in Banten. This research method is a quantitative survey method. The data collection method uses a questionnaire with a Likert scale. The data analysis method used is descriptive analysis and Structural Equation Modeling (SEM) analysis. The hypothesis test used in this study is the Chi-square test and the t test. The results of this study indicate that the variable self-efficacy has a major influence on student achievement motivation, then the peer support variable has a contribution to increase student achievement motivation. So, the latent variables peer support and self-efficacy have a positive effect on student achievement motivation.